Legal Liability for Personal Data Misuse in Digital Banking - Herryani, Mas Rara Tri Retno; Hikmah, Aufa Fajrul; Rahman, Irham (Hang Tuah Law Journal, 2026)
Digital transformation in the banking sector has led to the emergence of digital banking services that provide convenience, efficiency, and accessibility to the public. However, on the other hand, this development increases the risk of misuse of customer personal data, potentially resulting in material and immaterial losses. This study aims to analyze the forms of legal protection and legal accountability for misuse of customer personal data in banking institutions in the digital era. The research method used is normative legal research with a statutory and conceptual approach, through an examination of the Banking Law, Financial Services Authority regulations, Law Number 27 of 2022 concerning Personal Data Protection, and regulations related to consumer protection. The results show that the protection of customer personal data is part of citizens' constitutional rights that must be guaranteed by the state and electronic system providers, including digital banks. Legal liability for misuse of personal data can be imposed in the form of civil, administrative, and criminal liability, depending on the type of violation. Banks, as digital service providers, are obliged to apply the principle of prudence, maintain data confidentiality, and provide complaint and dispute resolution mechanisms for customers. The Personal Data Protection Law strengthens the legal basis for customer protection, but effective implementation and oversight remain challenges. Therefore, synergy between the government, the Financial Services Authority (OJK), and banking institutions is needed to strengthen data security systems and ensure legal certainty for customers facing the risk of personal data misuse in the digital era.